An Efficient Image Encryption Scheme Based on a Peter De Jong Chaotic Map and a RC4 Stream Cipher - Hanchinamani, Gururaj; Kulkarni, Linganagouda (3D research, 2015)
Security is a vital issue in communication and storage of the images and encryption is one of the ways to ensure the security. This paper proposes an efficient image encryption scheme based on a Peter De Jong chaotic map and a RC4 stream cipher. A Peter De Jong map is employed to determine the initial keys for the RC4 stream generator and also during permutation stage. The RC4 stream generator is utilized to generate the pseudo random numbers for the pixel value rotation and diffusion operations. Each encryption round is comprised of three stages: permutation, pixel value rotation and diffusion. The permutation is based on scrambling the rows and columns, in addition, circular rotations of the rows and columns in alternate orientations. The second stage circularly rotates each and every pixel value by utilizing M × N pseudo random numbers. The last stage carries out the diffusion twice by scanning the image in two different ways. Each of the two diffusions accomplishes the diffusion in two orientations (forward and backward) with two previously diffused pixels and two pseudo random numbers. The security and performance of the proposed method is assessed thoroughly by using key space, statistical, differential, entropy and performance analysis. Moreover, two rounds of the call to the encrypt function provide the sufficient security. The experimental results show that the proposed encryption scheme is computationally fast with high security.